2007
DOI: 10.3390/12040917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Carriers on the Production of Isoflavone Powder from Soybean Cake

Abstract: Abstract:The objectives of this study were to use soybean cake as the raw material for the production of isoflavone powder and compare the effects of different carriers as well as drying methods on the powder quality. Results showed that with spray drying, a level of 40 % maltodextrin as carrier produced the highest yield (mass) of isoflavone powder, followed by 10 % gelatin and 1 % sodium alginate. However, a reversed trend was observed for the isoflavone content. With 1 % sodium alginate, freeze drying gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the food industry MXs have been widely employed, providing different benefits such as the improvement of texture, reducing floury taste, as sweetness modifiers, controlling non-enzymatic browning, decreasing the freezing point in mixtures, as carriers and ingredients [3,5]. Likewise, because of their high solubility in water, MXs are widely employed in the encapsulation industry, mainly as additives in the drying processes [6,7]. The most important benefit of the addition of MX is increasing the T g of the food product and the subsequent preservation of the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the food industry MXs have been widely employed, providing different benefits such as the improvement of texture, reducing floury taste, as sweetness modifiers, controlling non-enzymatic browning, decreasing the freezing point in mixtures, as carriers and ingredients [3,5]. Likewise, because of their high solubility in water, MXs are widely employed in the encapsulation industry, mainly as additives in the drying processes [6,7]. The most important benefit of the addition of MX is increasing the T g of the food product and the subsequent preservation of the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, γ-PGA also finds potential application in a wide variety of fields including food, agriculture, cosmetics, medicine, and water treatment, which have been well reviewed , . Our earlier studies explored the application of γ-PGA as adsorbent for cationic dyes and heterocyclic amines , as well as carrier for encapsulation of lycopene and soy isoflavones . Previous studies on binding of heavy metals by γ-PGA have been restricted to metals ions such as Ni 2+ , Cu 2+ , Mn 2+ , Al 3+ , Cr 3+ , Hg 2+ , and U 4+ for water treatment .…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with those reported in the literature; however, it was stated that both drying processes led to a partial loss of compounds like small molecular carbonyls, furans, and phenols [ 38 ]. In another study it was reported that freeze drying can generate a more significant amount of isoflavone powder from soybean cake than vacuum drying and spray drying [ 39 ].…”
Section: Resultsmentioning
confidence: 99%